The influenza hemagglutinin stem antibody CR9114: Evidence for a narrow evolutionary path towards universal protection - Beukenhorst, Anna L.; Frallicciardi, Jacopo; Koch, Clarissa M.; Klap, Jaco M.; Phillips, Angela; Desai, Michael M.; Wichapong, Kanin; Nicolaes, Gerry A. F.; Koudstaal, Wouter; Alter, Galit; Goudsmit, Jaap (Frontiers in Virology, 2022)
Human monoclonal antibodies (hmAbs) that protect against all influenza A and B strains are considered the road to universal influenza vaccines. Based on publicly-available data, we analyze the mechanistic and structural basis of pan-influenza protection by CR9114, a hemagglutinin (HA) stem-reactive antibody that protects against influenza subtypes from groups A1, A2, and B. The mechanistic basis of CR9114’s universal protection is not limited to in vitro neutralization, as CR9114 also protects in vivo from strains that escape its neutralizing activity: avian H2 strains and influenza B. Fusion inhibition, viral egress inhibition, and activation of Fc-mediated effector functions are key contributors to CR9114’s universal protection. A comparative analysis of paratopes – between CR9114 (pan-influenza protection) and structurally similar VH1-69 hmAb CR6261 (influenza A1 protection) – pinpoints the structural basis of pan-influenza protection. CR9114’s heterosubtypic binding is conferred by its ability to bind HA with multiple domains: three HCDR loops and FR3. In contrast to other VH1-69 hmAbs, CR9114 uses a long and polar side chain of tyrosine (Y) residues on its HCDR3 for crucial H-bonds with H3, H5, and B HA. The recognition of a highly conserved epitope by CR9114 results in a high genetic barrier for escape by influenza strains. The nested, hierarchical structure of the mutations between the germline ancestor and CR9114 demonstrates that it is the result of a narrow evolutionary pathway within the B cell population. This rare evolutionary pathway indicates an immuno-recessive epitope and limited opportunity for vaccines to induce a polyclonal CR9114-like response.